Radiation synthesis and characterization of micro and nano particles of acrylated palm olein for use in drug delivery - Tajau, Rida (2013)
Emulsion polymerization and crosslinking reaction of acrylated palm olein (APO) in the presence of anionic and nonionic group surfactants were carried out by gamma irradiation. The critical micelle concentration (CMC) and formation of micro micelles as well their properties were determined their relationship to the control parameters such as APO and surfactant concentration, storage time and irradiation effect. The dynamic light scattering (DLS), fourier transform infrared (FTIR) spectroscopy and transmission electron microscopy (TEM) were used to characterize the size, the irradiation effect and the chemical structure of the micro and nanoparticle. Size of the APO micro and nanoparticles can be varied by changing the formulation and the irradiation dose. Size of the APO micro and nanoparticle is in the range of 77 to 500 nanometer (nm) when the system was irradiated with gamma ray at irradiation doses from 0.36 to 25 kGy. Using thymoquinone as a model bioactive compound, a drug loaded APO micro and nanoparticles were synthesized. Size of the thymoquinone-loaded APO micro or nanoparticle was in the range of 140 to 300 nanometer after irradiation using gamma irradiator. The presence of the bioactive and surface active compounds in the micro and nanomicelles determined the particle size and stability, and the bioactive release rate. This radiation-induced method provides a free initiator induced and easy to control process as compared to that of the classical or chemical initiator process. This study showed that radiation-induced initiator method which involves polymerization and crosslinking in the microemulsion is very promising for the synthesis of micro and nanoparticles.